2013
DOI: 10.1016/j.ijdevneu.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Investigation into the effects of prenatal alcohol exposure on postnatal spine development and expression of synaptophysin and PSD95 in rat hippocampus

Abstract: Ethanol is known as a potent teratogen responsible for the fetal alcohol syndrome characterized by cognitive deficits especially pronounced in juveniles but ameliorating in adults. Since the mechanisms of these deficits and following partial recovery are not fully elucidated, the aim of the present study was to investigate the process of synaptogenesis in the hippocampus over the first two months of life in control and fetal‐alcohol rats. Ethanol was delivered to the pregnant dams by intragastric intubation th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
25
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 68 publications
(84 reference statements)
3
25
0
Order By: Relevance
“…Adult, naive, female (n = 50) and male (n = 15) Wistar rats, obtained from the Animal Breeding Facility of the Gülhane Military Medical Academy (Ankara), were initially used for breeding. The animals’ maintenance conditions during breeding and rearing were the same as in our previous studies (Dursun et al, 2006; Elibol‐Can et al, 2014a,b). Rats were allowed to mate until a vaginal plug, an evidence of a successful fertilization, was observed.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Adult, naive, female (n = 50) and male (n = 15) Wistar rats, obtained from the Animal Breeding Facility of the Gülhane Military Medical Academy (Ankara), were initially used for breeding. The animals’ maintenance conditions during breeding and rearing were the same as in our previous studies (Dursun et al, 2006; Elibol‐Can et al, 2014a,b). Rats were allowed to mate until a vaginal plug, an evidence of a successful fertilization, was observed.…”
Section: Methodsmentioning
confidence: 99%
“…Starting from the GD7 throughout GD20, dams from A group were daily administered 6 g ethanol (96.5% v/v, Merck) per kg body weight by intragastric intubations using a stainless, curved feeding needle (18 ga, 3 in, Stoelting Co., Wood Dale, IL). The alcohol solution was prepared daily as a 25% (vol/vol) ethanol mixed with distilled water which was divided into two equal doses given to animals 1 h apart (Dursun et al, 2006; Elibol‐Can et al, 2014a,b). Animals in IC group received the same volume of fluid with sucrose substituted isocalorically for ethanol.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Cui et al (2010) have demonstrated a decrease in the number of dendritic spines for layer 5 (L5) PNs in the primary visual cortex, after prenatal exposure to alcohol. Other studies have demonstrated a decreased spine density or an alteration of spine development in the hippocampus after early exposure to alcohol (e.g., Berman and Hannigan, 2000; Elibol‐Can et al, 2014). The reduced spine density has been also observed after alcohol treatment of primary cultures of hippocampal neurons and has been attributed to alterations of the actin cytoskeleton (Romero et al, 2013).…”
Section: Discussionmentioning
confidence: 93%